Potential mechanisms underlying bluetongue virus emergence and spread - Thabet, Sara; Lajnef, Rim (Frontiers in Virology, 2024)
Bluetongue is a non-zoonotic arboviral disease transmitted by biting midges of the genus Culicoides. Among 1,347 Culicoides species, 30 are known to be vectors of the disease. Bluetongue affects domestic and wild ruminants across all continents, except the Antarctica, causing growing economic losses in livestock production and international trade. In this work, we focused on potential mechanisms underlying the bluetongue virus emergence and spread. Of these mechanisms, the emergence of novel serotypes makes vaccination controversial despite its effectiveness, along with the vector’s ability to acquire the virus and successfully transmit it, spatio-temporal adaptation, and identification of new transmission routes. We also discussed the predisposition of the vertebrate and invertebrate hosts to contract the virus, as well as factors hijacking vector population activity and abundance. Indeed, the ecological dynamics of biting midges strongly influence the ability of the virus to be transmitted and to cause epizootic into parts of the world never before affected, helped by interactions between the pathogen and its host in addition to multiple routes deployed to escape defense barriers in the target infected cells. The points raised in this review can help inform aspects of interest for future studies that may elucidate factors to consider in monitoring and controlling the expansion of Culicoides-transmitted arboviruses.